English language vocabulary development in high school students - Murgueitio Dioses, Dayanna Elizabeth; Pineda Mocha, Nayeli Margoth (Machala, Utmachala, 2023)
The purpose of this degree project is to design a system of activities using didactic resources which contribute positively to the development of vocabulary. The hypothesis on which the development of this project is based is that the implementation of a system of classes with the use of gamification as a didactic resource will improve the English vocabulary of the students of the Carmen Mora de Encalada High School. The quantitative paradigm is used with a pre-experimental approach, with the use of historical and empirical methods, such as observation, the execution of a diagnostic test (pre-test) and a comprehensive evaluation (post-test). The population analyzed was 26 students, 12 of whom were selected for the application of the method by means of the diagnostic test due to their low level of vocabulary. The application consisted of several classes using didactic resources, such as gamification, audiovisual materials, worksheets and virtual environments.
Este proyecto de titulación tiene como finalidad diseñar un sistema de actividades haciendo uso de recursos didácticos, los cuales aportan de manera positiva al desarrollo del vocabulario. La hipótesis en la que se basa el desarrollo de este proyecto es que la implementación de un sistema de clases con el uso de la gamificación como recurso didáctico, mejorará el vocabulario del inglés de los estudiantes de 2do A de bachillerato del Colegio Carmen Mora de Encalada. Se hace uso del paradigma cuantitativo con un enfoque pre experimental, con el empleo de métodos históricos y empíricos, tales como la observación, la ejecución de prueba diagnóstica (pre-test) y de una evaluación integral (post-test). La población que se analizó fue de 26 estudiantes, los cuales 12 fueron seleccionados para la aplicación del método mediante la prueba diagnóstica debido a su bajo nivel de vocabulario. La aplicación de métodos consistió en varias clases utilizando recursos didácticos, tales como la gamificación, materiales audiovisuales, worksheets y entornos virtuales.
Keywords: DIDACTIC RESOURCE; GAMIFICATION; DIAGNOSIS; METHOD; VOCABULARY; ACTIVITY SYSTEM; IMPLEMENTATION